Piracy and armed robbery at sea the legal framework for counter-piracy operations in Somalia and the Gulf of Aden - Geiss, Robin; Petrig, Anna. (Oxford : Oxford University Press, 2011)
This work describes the enforcement powers that states may use to repress piracy in the Gulf of Aden region. The piracy rules of the United Nations Convention on the Law of the Sea and the legal safeguards applicable to maritime interception operations are scrutinized before the analysis turns to the prosecution of pirates.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Piracy -- Aden, Gulf of -- Prevention; Maritime law -- Aden, Gulf of -- Criminal provisions